Massive Subcutaneous Emphysema, Pneumothorax and Pneumoscrotum: Diagnostic Dilemma on Autopsy - Vidhate, G S; Pathak, H; Kamble, R; Hosmani, A (International Journal of Medical Toxicology and Forensic Medicine, 2016)
Background: Subcutaneous emphysema is when gas or air in the layer under the skin. It literally means trapped air in the tissues beneath skin. It has characteristic crackling feel to touch, a sensation that has been described as similar to touching to Rice Krispies; this sensations under skin is called as subcutaneous crepitation. Case Report: A 50-years old male sustained injuries allegedly as a result of vehicular accident and was taken to a nearby private hospital. He was intubated there and then referred to a tertiary care hospital. He succumbed to death during transportation and was declared as brought dead on arrival. His body was brought for autopsy. Conclusion: There was massive subcutaneous emphysema, pneumothorax and pneumoscrotum. Their origin created a dilemma on autopsy due to various reasons. It is discussed in detail and tried to track the origin.